Sulfydryl-acrylate light-cured ink for DIW printing as well as preparation method and application of sulfydryl-acrylate light-cured ink
The ink, based on a mercapto-acrylate polymer system, solves the problems of rheological properties and oxygen inhibition in DIW printing, and realizes a biodegradable printing material with rapid curing and structural stability, suitable for biomedicine and tissue engineering.
Patent Information
- Application Number
- CN202511696229.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2026-01-23
AI Technical Summary
In existing additive manufacturing, direct-write (DIW) inks suffer from poor rheological properties, oxygen inhibition affecting curing quality, and structural instability caused by volume shrinkage. They are particularly difficult to meet the requirements for printing accuracy and stability in applications using biodegradable materials.
A thiol-acrylate polymer system is used, through the mixing of liquid acrylate poly(4-methyl-ε-caprolactone) and thiol-functionalized polyethylene glycol, combined with a UV photoinitiator, to form a fast-curing and biodegradable ink. The rheological properties and crosslinking network are optimized by thiol-olefin click chemistry.
It achieves rapid UV curing of ink, reduces oxygen inhibition effect, improves curing efficiency and double bond conversion rate, reduces volume shrinkage, improves dimensional accuracy and structural stability of printed components, and provides good biocompatibility, making it suitable for tissue engineering.
Smart Images

Figure CN121379244A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a printing ink and its preparation method and application, in particular to a mercapto-acrylate polymer system ink and its preparation method and application, and belongs to the technical field of polymer materials and additive manufacturing and its application. BACKGROUND
[0002] Additive manufacturing (AM), also known as three-dimensional printing, is a technology that builds three-dimensional objects by layering materials. With the aid of computer-aided design, it can achieve personalized and functional manufacturing of complex structures. It has shown great potential in the field of biomedical and tissue engineering (see“Application Research Progress of Three-dimensional Printing Technology in Tissue Engineering”, Chinese Journal of Biomedical Engineering, Vol. 40, No. 3, 2021, pp. 375-382).
[0003] Common additive manufacturing includes SLA (Stereolithography), DLP (Digital Light Processing), FDM (Fused Deposition Modeling) and DIW (Direct-ink-write printing), etc. Among them, DIW technology is of great concern due to its relatively low equipment cost, wide range of materials that can be used and simple operation. However, successful direct-write printing (DIW) requires the ink to have specific rheological properties, i.e. to exhibit shear thinning behavior during extrusion to smoothly pass through the nozzle, and to quickly recover the elastic modulus after extrusion to maintain the preset shape without collapse, while also requiring an efficient solidification mechanism to achieve permanent setting of the structure.
[0004] In the prior art, common methods for improving the rheological properties of inks include adding inorganic fillers to thermosetting systems, as described in the article "Interface engineering assisted 3D printing of silicone rubber composites" by Professor Gong Xinglong's team at the University of Science and Technology of China published in the journal Small: Hollow silver-coated glass microspheres (SHGMs) were introduced as fillers into a polydimethylsiloxane (PDMS) matrix to prepare a new type of silicone composite for direct ink writing (DIW) printing. When the filler content reached 74wt%, the composite precursor exhibited good shear thinning behavior and shape retention ability, meeting the requirements of DIW printing for material rheological properties. However, this method has the risk of nozzle blockage due to uneven dispersion of fillers, and the subsequent thermal curing process is time-consuming and energy-consuming, and may require additional steps to remove the porogen. In contrast, ultraviolet light curing systems, especially those based on acrylated polymers, can achieve rapid curing at room temperature, improving printing efficiency. However, the curing process is easily affected by the oxygen inhibition effect in the air, resulting in tacky surfaces and incomplete curing. In addition, the acrylate monomer undergoes a large volume contraction when homopolymerized, which generates internal stress in the printed part, affecting the dimensional accuracy and long-term stability (see "Oxygen inhibition problem in photocurable 3D printing technology", Polymer Communications, No. 8, 2020, pp. 45-51).
[0005] To overcome the above-mentioned defects, thiol-ene click chemistry, particularly thiol-acrylate systems, has been introduced into photocuring technology.
[0006] Thiol-acrylate systems undergo step-growth-chain transfer polymerization between thiol radicals and the olefinic functionality of acrylates, effectively reducing oxygen inhibition, increasing curing rate and double bond conversion, and forming a more uniform crosslinked network with reduced volume shrinkage (see "Thiol-ene click chemistry", Chemical Society Reviews, Vol. 39, No. 4, 2010, pp. 1235-1245), which provides a new approach to developing high-performance direct ink writing printing inks.
[0007] However, combining such systems with biodegradable polyester materials and optimizing the molecular design and ink formulation for the process requirements of direct ink writing printing remains a problem that needs further research and solution. SUMMARY
[0008] The present application aims to provide a biodegradable photocrosslinking ink for direct ink writing (DIW) printing that has good printability, rapid ultraviolet light curing ability, and can form a structurally stable and biodegradable elastic member.
[0009] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is as follows:
[0010] Firstly, the present application provides a kind of mercapto-acrylate polymer system ink for DIW printing 3D biodegradable elastic component, comprising the following components:
[0011] Liquid acrylate poly 4-methyl-epsilon-caprolactone, thiol functionalized polyethylene glycol and ultraviolet light initiator, wherein the liquid acrylate poly 4-methyl-epsilon-caprolactone has the following structure:
[0012] And m+n is 10-50;
[0013] The thiol functionalized polyethylene glycol has the following structure:
[0014] And x = 22.
[0015] Preferably, the ultraviolet light initiator is selected from one or more of Irgacure 184, TPO-L and DMPA.
[0016] Preferably, the liquid acrylate poly 4-methyl-epsilon-caprolactone is liquid acrylate poly 4-methyl-epsilon-caprolactone with polymerization degree m+n=10, the thiol functionalized polyethylene glycol is thiol functionalized polyethylene glycol with polymerization degree x=22, and the ultraviolet light initiator is TPO-L.
[0017] Secondly, the present application provides a preparation method of the above-mentioned ink, comprising the following steps:
[0018] Mixing the liquid acrylate poly 4-methyl-epsilon-caprolactone, the thiol functionalized polyethylene glycol and the ultraviolet light initiator to obtain, wherein:
[0019] The molar ratio of the liquid acrylate poly 4-methyl-epsilon-caprolactone to the thiol functionalized polyethylene glycol is 1:(0.25-1.0);
[0020] The mass of the ultraviolet light initiator accounts for (0.95-1.05)% of the mass of the liquid acrylate poly 4-methyl-epsilon-caprolactone.
[0021] Thirdly, the present application provides a method for preparing 3D biodegradable elastic component by DIW printing using the above-mentioned ink, comprising the following steps:
[0022] Loading the ink into the nozzle material bucket of DIW-3D printer, setting parameters including printing layer height, nozzle travel speed, extrusion speed and nozzle temperature, and then printing under ultraviolet light irradiation to obtain the 3D biodegradable elastic component.
[0023] On this basis, the application provides a 3D biodegradable elastic component printed by using the above-mentioned ink, which is prepared by the method for preparing a 3D biodegradable elastic component by printing by using the above-mentioned ink and DIW.
[0024] In addition, the application further provides a preparation method of liquid acrylate poly-4-methyl-epsilon-caprolactone, comprising the following steps:
[0025] Under the condition of ice water bath, the dichloromethane solution of 4-methylcyclohexanone is dropped into the dichloromethane solution of meta-chloroperoxybenzoic acid at a constant speed, wherein the mass ratio of 4-methylcyclohexanone to meta-chloroperoxybenzoic acid is 1: (1.5-3), after the dropping is completed, the reaction is carried out at room temperature for 24 hours, and 4-methyl-epsilon-caprolactone is obtained.
[0026] Under the protection of argon, 1,4-benzenedimethanol and 4-methyl-epsilon-caprolactone are mixed in a molar ratio of 1: (10-50), 0.1 % of isooctanoic acid stannous of 4-methyl-epsilon-caprolactone is added, and the polymerization reaction is carried out at a temperature of 120-140 DEG C for 6-24 hours, and poly-4-methyl-epsilon-caprolactone is obtained.
[0027] Under the condition of ice water bath, the dichloromethane solution of acryloyl chloride is dropped into the dichloromethane solution of poly-4-methyl-epsilon-caprolactone and triethylamine at a constant speed, wherein the molar ratio of poly-4-methyl-epsilon-caprolactone to acryloyl chloride and triethylamine is 1: (2.2-3): (2.0-3.0), after the dropping is completed, the reaction is carried out at room temperature for 24 hours, and the liquid acrylate poly-4-methyl-epsilon-caprolactone is obtained.
[0028] Preferably,
[0029] The mass ratio of 4-methylcyclohexanone to meta-chloroperoxybenzoic acid is 1: (1.85-2.15);
[0030] The poly-4-methyl-epsilon-caprolactone is liquid acrylate poly-4-methyl-epsilon-caprolactone with a polymerization degree m+n=10, and the molar ratio of liquid acrylate poly-4-methyl-epsilon-caprolactone with a polymerization degree m+n=10 to acryloyl chloride and triethylamine is 1: (2.15-2.25): (2.55-2.65;
[0031] The polymerization reaction time for preparing the poly-4-methyl-epsilon-caprolactone is 12-24 hours.
[0032] The application further provides a preparation method of thiol functionalized polyethylene glycol, comprising the following steps:
[0033] Dissolve polyethylene glycol and mercaptopropionic acid in toluene, add a catalytic amount of concentrated sulfuric acid, reflux at 90-130℃ for 12-24 hours, to obtain.
[0034] Preferably, the polyethylene glycol is polyethylene glycol with a number average molecular weight of 1000, and the molar ratio of the polyethylene glycol with a number average molecular weight of 1000 to the mercaptopropionic acid is 1: (4-6). Compared with the prior art, the present application has the outstanding beneficial effects and significant progress in that:
[0035] Firstly, the present application uses liquid 4-methyl-ε-caprolactone as raw material, and prepares acrylate-modified liquid poly 4-methyl-ε-caprolactone, i.e. liquid acrylate poly 4-methyl-ε-caprolactone (PMCLDA) through ring-opening polymerization and end group modification; and uses polyethylene glycol with a number average molecular weight of 1000 as raw material to prepare thiol-functionalized rheological modifier, i.e. thiol-functionalized polyethylene glycol (PEGSH) through esterification reaction; and the two are uniformly mixed with a photoinitiator to obtain a direct writing forming printing (DIW) special biodegradable photocrosslinking ink provided by the present application, which has good printability, fast ultraviolet light curing ability, and can form a stable and biodegradable elastic member structure. n The introduction of PEGSH effectively optimizes the rheological properties of the ink, making it a thiol-acrylate mixed ink suitable for DIW printing, which has suitable shear thinning properties and fast modulus recovery ability, and meets the stringent requirements of direct writing forming printing (DIW) on material rheological properties;
[0036] Secondly, the ink provided by the present application can be cured quickly under 365 nm ultraviolet light through thiol-acrylate click chemistry, thereby forming a 3D porous structure and degradable elastic member. Compared with the traditional acrylate homopolymerization crosslinking method, the introduction of thiol component significantly reduces the oxygen inhibition effect, improves the curing efficiency and double bond conversion rate, and improves the uniformity of the crosslinking network, thereby effectively improving the dimensional accuracy and structural stability of the printed member.
[0037] In addition, by introducing the hydrophilic rheological modifier PEGSH, not only the printing performance of the ink is optimized, but also the hydrophilic-hydrophobic balance of the obtained elastic member is effectively adjusted, providing a more suitable microenvironment for cell adhesion, proliferation and tissue growth, and showing good biocompatibility. Combined with the degradable properties of poly 4-methyl-ε-caprolactone, the ink shows wide research and application potential in the field of tissue engineering.
[0038] Finally, the present application provides a complete and coherent technical solution from the preparation of monomer raw materials to the final ink product, which includes the complete process flow of PMCLDA synthesis, functional modification, ink preparation and DIW printing forming. The process flow is clear, controllable and easy to implement, providing a reliable and innovative technical path for the manufacture of functional 3D biodegradable elastic members. Compared with the prior art, it shows outstanding beneficial effects and significant progress, and therefore has great popularization and application value. BRIEF DESCRIPTION OF DRAWINGS
[0039] In order to more clearly illustrate the technical solutions of the present application and the technical effects achieved by the present application, the following briefly introduces the drawings used in the embodiments of the present application.
[0040] Obviously:
[0041] The following described drawings are only part of the drawings in the embodiments of the present application, and for those skilled in the art, other drawings can also be obtained without creative labor on the basis of these drawings, but these other drawings also belong to the category of drawings required by the embodiments of the present application, wherein:
[0042] Figure 1 NMR spectrum of poly-4-methyl-ε-caprolactone (PMCL 10 ) with a polymerization degree m+n=10 and m=n;
[0043] Figure 2 NMR spectrum of liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) with a polymerization degree m+n=10 and m=n;
[0044] Figure 3 Fourier transform infrared spectrum of liquid poly-4-methyl-ε-caprolactone (PMCL 10 ) and liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) with a polymerization degree m+n=10 and m=n;
[0045] Figure 4 Gel permeation chromatogram of liquid poly-4-methyl-ε-caprolactone (PMCL 10 ) and liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) with a polymerization degree m+n=10 and m=n;
[0046] Figure 5 NMR spectrum of polyethylene glycol (PEG n SH) with M 22 =1000 and a polymerization degree x=22;
[0047] Figure 6 Fourier transform infrared spectrum of polyethylene glycol with Mn=1000 and thiol-functionalized polyethylene glycol (PEG-SH) with x=22; 22
[0048] Figure 7 Viscosity change graph of different ratio inks in rotational oscillation mode;
[0049] Figure 8 Shear stress-shear rate graph of different ratio inks in rotational continuous scan mode;
[0050] Figure 9 Viscosity-shear rate graph of different ratio inks in rotational continuous scan mode;
[0051] Figure 10 In-situ infrared three-dimensional continuous spectrum graph of different ratio inks in photopolymerization process;
[0052] Figure 11 Double bond monomer conversion rate graph of different ratio inks in photopolymerization process;
[0053] Figure 12 In-situ optical rheological test graph of different formula inks in photopolymerization process;
[0054] Figure 13 Device and process schematic diagram for DIW printing using thiol-acrylate polymer ink, wherein:
[0055] Figure 13-1 3D model graph established by Biomaker software;
[0056] Figure 13-2 Schematic diagram of the three-dimensional structure of the DIW printing device;
[0057] Figure 13-3 Schematic diagram of the working of the nozzle of the DIW printing device;
[0058] Figure 14 Photo set of different components obtained by DIW printing using the thiol-acrylate polymer ink SH75 prepared in Example 3.3, wherein:
[0059] Figure 14-1 a is 1 # 3D model graph of the component;
[0060] Figure 14-1 b is 1 # Photo of the physical component;
[0061] Figure 14-2 a is 2 # 3D model diagram of component 2;
[0062] Figure 14-2 b is 2 # Physical photo of component;
[0063] Figure 14-3 a is 3 # 3D model diagram of component;
[0064] Figure 14-3 b is 3 # Physical photo of component;
[0065] Figure 14-4 a is 4 # 3D model diagram of component;
[0066] Figure 14-4 b is 4 # Physical photo of component;
[0067] Figure 15 Cycle compression performance test diagram of 3D grid component SH25-7, SH50-3, SH75-4;
[0068] Figure 16 Contact angle test diagram of 3D grid component SH25-7, SH50-3, SH75-4.
[0069] Figure 17 In vitro degradation curve diagram of 3D grid component SH25-7, SH50-3, SH75-4 and PCL / poly-ε-caprolactone film;
[0070] Figure 18 In vitro cell proliferation column chart of 3D grid component SH25-7, SH50-3, SH75-4 and PCL / poly-ε-caprolactone film, wherein:
[0071] “*” represents , there is a statistically significant difference;
[0072] “***” represents , there is a very significant statistical difference;
[0073] “ns” represents no statistical difference. DETAILED DESCRIPTION
[0074] In order to make the technical solutions, beneficial effects and significant progress of the present application clearer and more comprehensive, below, the technical solutions provided by the present application will be clearly and completely described through specific examples and their effect examples. Obviously, all the examples described below and their corresponding effect examples are only part of the examples and effects of the present application, not all.
[0075] Based on the embodiments and effect examples provided by the present application, all other embodiments and effect examples obtained by those skilled in the art without creative labor fall within the scope of the present application.
[0076] It should be noted that:
[0077] The terms "first", "second", etc. in the claims, specification and cases and effect examples of the embodiments of the present application are only used to distinguish different objects, and are not used to describe a specific order; in addition, the term "comprising" and any variations thereof are intended to cover non-exclusive inclusion, for example, a process, method, system, product or device, etc. not only includes a series of listed steps or units, but also optionally includes steps or units not listed, or optionally includes other operation steps or units inherent to the process, method, product or device.
[0078] It should be understood that:
[0079] In the description of the embodiments of the present application, some basic operation terms commonly used in the art will be used, such as "stirring", "dissolving" and the like. For these terms, a broad understanding should be made, that is, it can be a conventional operation by various conventional devices and instruments in the art, or it can be a program-controlled operation, unmanned automatic operation, etc. by the latest devices. Unless otherwise specified, those skilled in the art should understand the specific meaning of the above terms in the present application according to the specific situation, and adopt the specific operation method to achieve its operation purpose.
[0080] It should be noted that the following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some cases and comparative examples. In addition, various instruments, devices, raw and auxiliary materials, reagents and standards, etc. involved in the following specific embodiments are commercially available unless otherwise specified.
[0081] The technical solutions of the present application will be described in detail below with specific embodiments. Embodiment 1
[0082] The present embodiment provides a liquid acrylic ester poly-4-methyl-ε-caprolactone (abbreviated as: PMCLDA).
[0083] The liquid acrylic ester poly-4-methyl-ε-caprolactone (PMCLDA) provided by the present embodiment is made by the following method:
[0084] Preparation route:
[0085] ;
[0086] ;
[0087] ;
[0088] That is, 4-methylcyclohexanone is used as raw material, 4-methyl-ε-caprolactone (MeCL) monomer is prepared by Baeyer-Villiger oxidation reaction (abbreviation: BV), and then the corresponding liquid polymer poly-4-methyl-ε-caprolactone (abbreviation: PMCL) is prepared by ring-opening polymerization, and then the corresponding liquid acrylic ester poly-4-methyl-ε-caprolactone (PMCLDA) is obtained by end double bond functional modification, which specifically includes the following steps:
[0089] Under the condition of ice water bath, the dichloromethane solution of 4-methylcyclohexanone is uniformly dropped into the dichloromethane solution of meta-chloroperoxybenzoic acid, wherein the mass ratio of 4-methylcyclohexanone to meta-chloroperoxybenzoic acid is 1: (1.5-3), after the dropping is completed, the reaction is carried out at room temperature for 24 hours, and the transparent liquid 4-methyl-ε-caprolactone monomer (abbreviation: MeCL) is obtained;
[0090] Under the protection of argon, 1,4-benzenedimethanol and 4-methyl-ε-caprolactone (MeCL) are mixed in a molar ratio of 1: (10-50), and 0. (0.95-1.05) % of the catalyst stannous octoate Sn(Oct)2 based on the mass of 4-methyl-ε-caprolactone (MeCL) is added, and the polymerization reaction is carried out at a temperature of 120-140℃ for 12-24 hours, and the transparent liquid polymer poly-4-methyl-ε-caprolactone (abbreviation: PMCL) is obtained;
[0091] Under the condition of ice water bath, the dichloromethane solution of acryloyl chloride (abbreviation: AC) is uniformly dropped into the dichloromethane solution of poly-4-methyl-ε-caprolactone (PMCL) and triethylamine, wherein the molar ratio of poly-4-methyl-ε-caprolactone (PMCL) to acryloyl chloride and triethylamine is 1: (2.2-3) : (2.0-3), after the dropping is completed, the reaction is carried out at room temperature for 24 hours, and the liquid transparent liquid acrylic ester poly-4-methyl-ε-caprolactone (PMCLDA) is obtained.
[0092] In the above preparation process, the preferred mass ratio of 4-methylcyclohexanone to meta-chloroperoxybenzoic acid is 1:2, and the preferred molar ratio of poly-4-methyl-ε-caprolactone (PMCL) to acryloyl chloride (AC) and triethylamine is 1:2.2:2.6.
[0093] To further help understand the technical solutions provided by the present embodiment and the specific operation process and the technical effects that can be obtained by the present embodiment, the following will further illustrate the preparation method provided by the present embodiment and the technical effects that can be obtained by the present embodiment through specific preparation examples.
[0094] Of course, those skilled in the art should understand that the preparation examples described below are only illustrative and not limiting, and therefore should not limit the scope of protection required by the present application. Preparation Example 1.1
[0095] The present preparation example provides a liquid acrylate poly-4-methyl-ε-caprolactone (abbreviated as: PMCL 10 DA).
[0096] 1) Preparation of 4-methyl-ε-caprolactone monomer
[0097] Under the condition of ice water bath, 60.00 g of 4-methylcyclohexanone was dissolved in 50-100 mL of dichloromethane, and then was added to a 400-500 mL dichloromethane solution containing 120.00 g of meta-chloroperoxybenzoic acid (abbreviated as: m-CPBA) (i.e. the mass ratio of 4-methylcyclohexanone to m-CPBA is 1:2) at a constant speed. After the addition was completed, the reaction was carried out at room temperature for 24 hours, and then the solid was removed by suction filtration. The crude product was washed with saturated sodium thiosulfate, sodium bicarbonate and sodium chloride aqueous solution in turn, and then a small amount of anhydrous magnesium sulfate was added and stirred for 2 hours. The solid was removed by suction filtration, and the excess dichloromethane was removed by rotary evaporation under reduced pressure at 100-110°C to obtain transparent 4-methyl-ε-caprolactone (MeCL) monomer.
[0098] 2) Preparation of poly-4-methyl-ε-caprolactone (PMCL 10 )
[0099] Under the protection of argon, 4.31 g of initiator 1,4-benzenedimethanol (abbreviated as: BDM) was mixed with 40.00 g of 4-methyl-ε-caprolactone (MeCL) monomer (i.e. the molar ratio of BDM to MeCL is 1:10), and then the temperature was raised to 60°C. After vacuumizing for 3-6 hours, 40.00 mg of isooctanoic acid stannous Sn(Oct)2 (its mass is 0.1wt% of the mass of MeCL) was added as a catalyst under argon atmosphere, and the polymerization reaction was continued at 130°C for 12-24 hours to obtain a polymer. Then, an appropriate amount of dichloromethane was added for dilution, and petroleum ether was added in a proportion of polymer: petroleum ether = 1: (6-10) for sedimentation, and then vacuum drying was carried out to obtain liquid poly-4-methyl-ε-caprolactone (PMCL 10 ) with a polymerization degree m+n=10 and m=n.
[0100] Figure 1 The nuclear magnetic resonance hydrogen spectrum (abbreviated as: 10 H NMR) of poly-4-methyl-ε-caprolactone (PMCL 1 ) with a polymerization degree m+n=10 and m=n.
[0101] From Figure 1 It can be seen that:1H NMR (400 MHz, CDC13, TMS): δ = 7.36 ppm (Ha, s, -C6H4-, 4H), 5.11 ppm (Hb, s, -C6H4CH2-, 4H), 4.12 ppm (He, m, -CH2CH2O-, 2H), 3.69 ppm (He', m, -CH2CH2O-, 2H), 2.33 ppm (Hc, m, -COCH2-, 2H), 0.94 ppm (Hd, s, -CHCH3CH2-, 3H), the degree of polymerization m+n = 10 and theoretically m = n = 5.
[0102] 3) The liquid acrylate poly 4-methyl-ε-caprolactone (PMCL 10 DA) with the degree of polymerization m+n = 10 and m = n
[0103] Under the protection of argon, 13.00 g of PMCL 10 DA) and 2.44 g of triethylamine (referred to as: TEA) were dissolved in 80 mL of dichloromethane, and a 50 mL dichloromethane solution containing 1.85 g of acryloyl chloride (AC) was added at a constant speed under an ice water bath, wherein the molar ratio of PMCL 10 DA), acryloyl chloride (AC) and triethylamine (TEA) was 1:2.2:2.6. After the addition was completed, the product was reacted at room temperature for 24 hours. After treatment, a certain amount of anhydrous potassium carbonate was added and stirred for 3 hours, then the solid was removed by centrifugation, 2 mL of hydrochloric acid was added and stirred for 30 minutes, then 200-300 mL of dichloromethane was added for dilution, then saturated sodium bicarbonate aqueous solution, deionized water and saturated sodium chloride solution were used in sequence for washing, finally a small amount of anhydrous magnesium sulfate was added and stirred for drying for 2 hours, the solid was removed by suction filtration, the excess dichloromethane was removed by rotary evaporation, then petroleum ether was added in a proportion of product: petroleum ether = 1: (6-10) for sedimentation, and then vacuum drying was performed to obtain the liquid acrylate poly 4-methyl-ε-caprolactone (PMCL 10 DA) with the degree of polymerization m+n = 10 and m = n.
[0104] Figure 2 The liquid acrylate poly 4-methyl-ε-caprolactone (PMCL 10 DA) with the degree of polymerization m+n = 10 and m = n. 1 H NMR).
[0105] From Figure 2As can be seen in 1H NMR (400 MHz, CDCl3, TMS): δ=7.36 ppm (Ha, s, -C6H4-,4H), 6.28-6.42 ppm (Hh, d, -COOCH=CH2, 1H), 5.98-6.14 ppm (Hf, d, -COOCH=CH2,1H), 5.72-5.81 ppm (Hg, d, -COOCH=CH2, 1H), 5.11 ppm (Hb, s, -C6H4CH2-, 4H), 4.25ppm (He', m, -CH2CH2O-,2H), 4.10 ppm (He, m, -CH2CH2O-, 2H), 2.31 ppm (Hc, m, -COCH2-, 2H), 0.94 ppm (Hd, s, -CHCH3CH2-,3H), degree of polymerization m+n=10 and theoretically m=n=5.
[0106] Figure 3 Liquid poly(4-methyl-ε-caprolactone) (PMCL) with degree of polymerization m+n=10 and m=n 10 ) and liquid acrylate poly(4-methyl-ε-caprolactone) (PMCL) 10 Fourier Transform Infrared Spectroscopy (FTIR) of DA.
[0107] from Figure 3 It can be seen from this that: PMCL 10 The FTIR spectrum of DA at wavenumber 1619 -1 and 1636 cm -1 The presence of a C=C stretching vibration absorption peak at this point proves that PMCL 10 It was successfully modified by double bonding.
[0108] Figure 4 Liquid poly(4-methyl-ε-caprolactone) (PMCL) with degree of polymerization m+n=10 and m=n 10 ) and liquid acrylate poly(4-methyl-ε-caprolactone) (PMCL) 10 Gel permeation chromatogram (GPC chromatogram) of DA.
[0109] from Figure 4 It can be seen from this that: liquid poly-4-methyl-ε-caprolactone (PMCL) 10 ) and liquid acrylate poly(4-methyl-ε-caprolactone) (PMCL) 10 The GPC values of DA all showed a single normal distribution, indicating that the liquid acrylate poly(4-methyl-ε-caprolactone) (PMCL) prepared in Example 1 was normal.10 The structure of the DA) is controllable. Preparation Example 1.2
[0110] The present preparation example provides a liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 50 DA) with a polymerization degree m+n=50.
[0111] The present preparation example provides a liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 50 DA) with a polymerization degree m+n=50.
[0112] The present preparation example provides a liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 50 ) with a polymerization degree m+n=50.
[0113] The mass of the initiator 1,4-benzenedimethanol (BDM) is 0.86 g, the molar ratio of BDM to 4-methyl-ε-caprolactone monomer (MeCL) is 1:50, and the addition amount of the catalyst stannous octoate Sn(Oct)2 is 0.2 wt% of the mass of the MeCL monomer. Finally, a liquid poly-4-methyl-ε-caprolactone (PMCL 50 ) with a polymerization degree m+n=50 (theoretically m=n=25) is obtained.
[0114] The present preparation example provides a liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 50 DA) with a polymerization degree m+n=50.
[0115] The mass of the initiator 1,4-benzenedimethanol (BDM) is 0.86 g, the molar ratio of BDM to 4-methyl-ε-caprolactone monomer (MeCL) is 1:50, and the addition amount of the catalyst stannous octoate Sn(Oct)2 is 0.2 wt% of the mass of the MeCL monomer. Finally, a liquid poly-4-methyl-ε-caprolactone (PMCL 50 ) with a polymerization degree m+n=50 (theoretically m=n=25) is obtained. 50 The mass of the initiator 1,4-benzenedimethanol (BDM) is 0.86 g, the molar ratio of BDM to 4-methyl-ε-caprolactone monomer (MeCL) is 1:50, and the addition amount of the catalyst stannous octoate Sn(Oct)2 is 0.2 wt% of the mass of the MeCL monomer. Finally, a liquid poly-4-methyl-ε-caprolactone (PMCL 50 DA) with a polymerization degree m+n=50 (theoretically m=n=25) is obtained. Preparation Example 1.3
[0116] The present preparation example provides a liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 80 DA) with a polymerization degree m+n=80.
[0117] The preparation example provides liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 80 The preparation method and steps of DA are basically same with those of the preparation example 1.1, except that the feeding amount / ratio in the preparation process is different, wherein:
[0118] The poly-4-methyl-ε-caprolactone (PMCL 80 ) with a polymerization degree m+n=80 is prepared by:
[0119] The amount of initiator 1,4-benzene dimethanol (BDM) is 0.45 g (4.31 g in the preparation example 1.1), namely the molar ratio of BDM to 4-methyl-ε-caprolactone (MeCL) monomer is 1:80 (1:10 in the preparation example 1.1), the amount of catalyst stannous octoate Sn(Oct)2 is 0.5 wt% of the mass of MeCL monomer (0.1 wt% in the preparation example 1.1), and finally the obtained product is liquid poly-4-methyl-ε-caprolactone (PMCL 80 ) with a polymerization degree m+n=80 (theoretically m=n=40). Example 2
[0120] The example provides a thiol-functionalized polyethylene glycol (PEGSH).
[0121] The thiol-functionalized polyethylene glycol (PEGSH) is made by the following method:
[0122] The synthesis route is as follows:
[0123] ;
[0124] The polyethylene glycol and mercaptopropionic acid are dissolved in toluene, a catalytic amount of concentrated sulfuric acid is added, and the reaction is refluxed at 90-130 ℃ for 12-24 hours.
[0125] In the above reaction, the preferred molar ratio of polyethylene glycol to mercaptopropionic acid is 1:(4-6).
[0126] To further help understand the technical solutions provided by the example and the specific operation process and the technical effects that can be obtained by the example, the following will further illustrate the preparation method provided by the example and the technical effects that can be obtained by the example through specific preparation examples.
[0127] Of course, those skilled in the art should understand that the preparation examples specifically described below are only illustrative and not limiting, and therefore should not limit the scope of protection required by the present application. Preparation example 2.1
[0128] This embodiment provides a rheology modifier, thiol-functionalized polyethylene glycol (PEG), with a degree of polymerization x=22. 22 SH).
[0129] This embodiment provides thiol-functionalized polyethylene glycol (PEG) with a degree of polymerization x=22. 22 SH is prepared by the following method.
[0130] 10.00 g of a number-average molecular weight of 1000 (i.e., M n Polyethylene glycol (PEG) with a degree of polymerization (x=1000) and 4.25 g of mercaptopropionic acid were dissolved in 100–150 mL of toluene (molar ratio 1:4). The mixture was heated to 60 °C, and after the reactants were completely dissolved, two drops of concentrated sulfuric acid (98% by weight) were added to the reaction solution. The mixture was refluxed at 90–130 °C for 12–24 hours. Heating was stopped when no more water was observed to be generated in the reactor. After post-treatment, excess toluene was removed by rotary evaporation, followed by dilution with 100 mL of dichloromethane. The organic phase was then washed successively with saturated NaHCO3 aqueous solution and saturated NaCl solution. A small amount of anhydrous magnesium sulfate was added, and the mixture was stirred and dried for 2 hours. The solid was removed by filtration, and excess dichloromethane was removed by rotary evaporation. The mixture was then precipitated with sufficient ice-cold diethyl ether and dried under vacuum to obtain thiol-functionalized polyethylene glycol (PEG) with a degree of polymerization (x=22). 22 SH).
[0131] Figure 5 For M n =1000 polyethylene glycol (PEG) and thiol-functionalized polyethylene glycol (PEG) with a degree of polymerization of x=22 22 The proton NMR spectrum of SH.
[0132] from Figure 5 It can be seen from this:
[0133] PEG(M) n =1000) of polyethylene glycol 1 H NMR (400 MHz, CDCl3, TMS): δ = 3.66 ppm (H a ,m, -CH2C H 2OH, 2H), 3.66 ppm (H b (, m, -OCH2CH2O-, 2H).
[0134] Thiol-functionalized polyethylene glycol (PEG) with a degree of polymerization x=22 22 SH) 1 H NMR (400 MHz, CDCl3, TMS): δ = 4.27 ppm (H b’ , m, -CH 2COO-, 2H), 3.66 ppm (H a , m, -OCH2CH2O-, 2H), 2.79 ppm (H c ,m, -C H 2CH2SH, 2H), 2.69 ppm (H d , m, -CH2C H 2SH, 2H), 1.69 ppm (H a , m, -CH2S H , 1H), wherein the PEG molecular weight M n = 1000, and the polymerization degree x = 22.
[0135] Figure 6 A Fourier transform infrared spectrum (FTIR) of a polyethylene glycol (PEG) with Mn = 1000 and a thiol-functionalized polyethylene glycol (PEG 22 SH) with x = 22.
[0136] As can be seen from Figure 6 , the PEG 22 SH has an S-H stretching vibration absorption peak at a wave number of 2570 cm -1 , which proves that the reactant PEG (Mn = 1000) has been successfully modified by mercapto. Preparation Example 2.2
[0137] The present preparation example provides a thiol-functionalized polyethylene glycol (PEG 33 SH) with a polymerization degree x = 33.
[0138] The preparation method and steps of the thiol-functionalized polyethylene glycol (PEG 33 SH) with a polymerization degree x = 33 are basically the same as those of the PEG 22 SH prepared in Preparation Example 2.1, except for the specific materials and specifications used and the reaction control parameters, wherein:
[0139] The raw material used is polyethylene glycol (PEG) with a number average molecular weight Mn = 1500 (x = 33) (in Preparation Example 2.1, the PEG has Mn = 1000);
[0140] Since the molecular weight of the raw material PEG (Mn=1500) in this preparation example is different from that of the raw material PEG (Mn=1000) in Preparation Example 2.1, the molar ratio of PEG (Mn=1500) to 3-mercaptopropionic acid in this preparation example is changed, i.e., the molar ratio of PEG (Mn=1000) to 3-mercaptopropionic acid in Preparation Example 2.1 is 1:4, and becomes the molar ratio of PEG (Mn=1500) to 3-mercaptopropionic acid in this preparation example is 1:6;
[0141] In addition, the reflux reaction is 6-24 hours (12-24 hours in Preparation Example 2.1), i.e., the lower limit of the reflux time can be shorter. Example 3
[0142] This example provides a mercapto-acrylate polymer series ink for DIW printing.
[0143] The mercapto-acrylate polymer series ink provided in this example is prepared by the following method:
[0144] Take 2.00 g of PMCL 10 DA, according to the functional group molar ratio of mercapto group:double bond=0.25:1, and 200 mg of PEG 22 SH prepared in Preparation Example 2.1, and then follow-up operations, i.e., add 20 mg of liquid ultraviolet light initiator TPO-L (TPO-L accounts for (0.95-1.05)% of the mass of PMCL 10 DA), or accounts for (0.95-1.05)% of the mass of PMCL 10 DA), or accounts for (0.95-1.05)% of the mass of PMCL 10 DA, and one or more of the liquid ultraviolet light initiator Irgacure 184 and DMPA accounting for (0.95-1.05)% of the mass of PMCL 50 DA, and 40 mg of PEG 22 SH prepared in Preparation Example 2.1, and then follow-up operations according to the preparation method of SH25, i.e., the ink SH50 can be prepared;
[0145] The preparation method of ink SH50 is basically the same as that of SH25, except that the PMCL 10 DA in SH25 is replaced by PMCL 50 DA prepared in Preparation Example 1.2, and 40 mg of PEG 22 SH prepared in Preparation Example 2.1, and then follow-up operations according to the preparation method of SH25, i.e., the ink SH50 can be prepared;
[0146] The preparation method of ink SH80 is also basically the same as that of SH25, except that the PMCL 10 DA in SH25 is replaced by PMCL 80 DA prepared in Preparation Example 1.3, and 25 mg of PEG 22SH, and then the subsequent operation method of SH25 is performed, so that the ink SH80 is prepared.
[0147] To further help understand the technical solutions provided by the present embodiment and the specific operation process and the technical effects that can be obtained, the effects of the ink provided by the present embodiment are further described below through a specific effect example.
[0148] Of course, those skilled in the art should understand that the effect example described below is only illustrative and not limiting, and should not limit the scope of protection claimed by the present application. Effect Example 3.1
[0149] The present effect example is used to show the curing rate of the series of inks prepared by the present embodiment.
[0150] The above three different formula inks SH25, SH50 and SH80 prepared by the present embodiment are respectively placed in transparent glass dishes, and a 365 nm ultraviolet light source is turned on to observe and record their respective curing conditions, and the test results are listed in Table 1 below.
[0151] Table 1
[0152]
[0153] Table 1 shows the curing conditions of inks composed of liquid acrylate poly-4-methyl-ε-caprolactone (PMCLDA) with different degrees of polymerization and rheological modifier PEG 22 SH and ultraviolet light initiator TPO-L under 365 nm ultraviolet light irradiation.
[0154] From the data listed in Table 1, it can be seen that:
[0155] The additive body is PMCL 10 DA has the fastest curing rate, and can be completely cured within 10 seconds; as the molecular weight of the additive body increases, the time required for complete curing also increases, and when the degree of polymerization of the additive body exceeds 50, the time required for complete curing will be greater than 15 seconds. Obviously, too slow curing rate is not conducive to the maintenance of the structure of the printed component and the guarantee of the forming precision during printing; in addition, too low degree of polymerization of the additive body will also affect the elasticity of the subsequent printed component, and therefore the degree of polymerization of the additive body is preferably 10-50.
[0156] Effect Example 3.2
[0157] The present effect example is used to show the extrusion of inks made of the additive body liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) prepared in the above Preparation Example 1.1 and different rheological modifiers PEGSH.
[0158] Take 2.00 g of PMCL prepared in Preparation Example 1.1 10 DA, according to the functional group molar ratio of sulfhydryl group: double bond = 0.25:1, with 200 mg of rheology modifier PEG prepared in Preparation Example 2.1 22 SH, and then add 20 mg of liquid ultraviolet light initiator TPO-L (accounting for 1 wt% of the mass of PMCL 10 DA), and then prepare the ink SH25 by oscillation and ultrasonic circulation.
[0159] According to the same preparation method of the above ink SH25, except that the rheology modifier therein is replaced by the rheology modifier PEG 33 SH prepared in Preparation Example 2.2, and then according to the subsequent preparation method of SH25, the ink SH33 can be prepared;
[0160] The above two inks SH25 and SH33 are respectively filled into a syringe equipped with a 25 G needle, and the syringe is forced to perform extrusion test, and the results are shown in Table 2.
[0161] Table 2
[0162]
[0163] Table 2 shows the extrusion of the ink prepared by the additive main body liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) prepared in Preparation Example 1.1 and different rheology modifiers PEGSH.
[0164] As can be seen from the data listed in Table 2:
[0165] The rheology modifier PEG 22 SH prepared by PEG with Mn=1000 can be uniformly mixed with the additive main body liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) and liquid ultraviolet light initiator TPO-L, and the prepared ink can maintain good "wax-like" characteristics and can be smoothly extruded from the needle after being subjected to pressure;
[0166] When the molecular weight of PEGSH increases, such as PEG 33 SH prepared by PEG with Mn=1500, and the ink composed of the same additive main body such as PMCL 10 DA, and the same ultraviolet light initiator, due to its highly crystalline structure, the ink maintains a "wax-like" state and is difficult to be extruded after being subjected to pressure.
[0167] Therefore, it can be considered that the rheology modifier PEG 22SH is more suitable as a rheology modifier. Effect Example 3.3
[0168] This effect example is used to show the rheological properties of the ink prepared by the additive main body liquid acrylate poly 4-methyl-ε-caprolactone (PMCL 10 DA) and the rheology modifier PEG 22 SH prepared by Preparation Example 2.1 in different proportions.
[0169] Experimental method:
[0170] Take 2.00 g of the additive main body liquid acrylate poly 4-methyl-ε-caprolactone (PMCL 10 DA) prepared in Preparation Example 1.1, do not add rheology modifier PEG 10 SH, only add 20 mg of liquid ultraviolet light initiator TPO-L (1 wt% of PMCL 10 DA), shake, ultrasonic circulation to mix evenly, named as ink SH0;
[0171] Take 2.00 g of the additive main body liquid acrylate poly 4-methyl-ε-caprolactone (PMCL 10 DA) prepared in Preparation Example 1.1, according to the functional group molar ratio of thiol group:double bond=0.25:1, mix with 200 mg of rheology modifier PEG 22 SH obtained by Preparation Example 2.1, and then add 20 mg of liquid ultraviolet light initiator TPO-L (1 wt% of PMCL 10 DA), shake, ultrasonic circulation to mix evenly, named as ink SH25;
[0172] Take 2.00 g of the additive main body liquid acrylate poly 4-methyl-ε-caprolactone (PMCL 10 DA) prepared in Preparation Example 1.1, according to the functional group molar ratio of thiol group:double bond=0.5:1, mix with 400 mg of rheology modifier PEG 22 SH obtained by Preparation Example 2.1, and then add 20 mg of liquid ultraviolet light initiator TPO-L (1 wt% of PMCL 10 DA), shake, ultrasonic circulation to mix evenly, named as ink SH50;
[0173] Take 2.00 g of the additive main body liquid acrylate poly 4-methyl-ε-caprolactone (PMCL 10 DA) prepared in Preparation Example 1.1, according to the functional group molar ratio of thiol group:double bond=0.75:1, mix with 600 mg of rheology modifier PEG 22SH mixed, then 20 mg of liquid UV initiator TPO-L (1 wt% of PMCLDA) was added, and the mixture was mixed evenly by shaking and ultrasonic circulation, and was named as ink SH75;
[0174] 2.00 g of the additive main body liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) prepared in Preparation Example 1.1 was taken, and was mixed with 800 mg of the rheological modifier PEG 22 SH, then 20 mg of liquid UV initiator TPO-L (1 wt% of PMCLDA) was added, and the mixture was mixed evenly by shaking and ultrasonic circulation, and was named as ink SH100.
[0175] Figure 7 The viscosity change graph of the ink with different proportions in the rotating shaking mode.
[0176] It can be seen from Figure 7 that:
[0177] The acrylate polymer ink SH0 containing no rheological modifier PEG 22 SH prepared in Preparation Example 2.1 and only containing the additive main body liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) prepared in Preparation Example 1.1 has a viscosity of only 2.1 Pa·s;
[0178] When the rheological modifier PEG 22 SH prepared in Preparation Example 2.1 is added to the acrylate polymer ink system to form a thiol-acrylate polymer ink, the viscosity of the ink is greatly improved, and the viscosity of the ink SH25 reaches 219.7 Pa·s. The viscosity of the thiol-acrylate polymer ink system increases with the increase of the content of the modifier PEG 22 SH in the ink, and the viscosity of the ink SH100 can reach a high value of 889.4 Pa·s.
[0179] Figure 8 The shear stress-shear rate relationship graph of the ink with different proportions in the rotating continuous scanning mode.
[0180] It can be seen from Figure 8 that:
[0181] For the acrylate polymer ink containing no rheological modifier and only containing the additive main body liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10For acrylate polymer inks SH0 composed of DA), the shear stress and shear rate are linearly related, exhibiting typical Newtonian fluid characteristics, which is not suitable for DIW printing;
[0182] For the addition of the rheology modifier PEG obtained from Preparation Example 2.1 22 For inks SH25, SH50, SH75 and SH100, which constitute the mercapto-acrylate polymer ink system, their shear stress-shear rate curves deviate from linearity, exhibiting typical pseudoplastic fluid characteristics.
[0183] Figure 9 This is a viscosity-shear rate relationship graph for inks with different ratios in rotating continuous scanning mode.
[0184] from Figure 9 It can be seen from this:
[0185] For additive substrates containing only the liquid acrylate poly(4-methyl-ε-caprolactone) prepared in Example 1.1 without the addition of rheology modifiers, 10 For acrylate polymer inks SH0 composed of DA), the viscosity is constant;
[0186] For the addition of the rheology modifier PEG obtained from Preparation Example 2.1 22 For inks that form a thiol-acrylate polymer system, the viscosity decreases significantly with increasing shear rate, exhibiting a clear shear-thinning characteristic, indicating that the rheology modifier PEG... 22 The addition of SH effectively improves the rheological properties of the mixed ink. Its shear thinning property ensures that the ink can effectively reduce its extrusion resistance during the printing process, thus allowing it to be extruded smoothly. Example of effect 3.4
[0187] This example demonstrates the additive substrate liquid poly(4-methyl-ε-caprolactone) (PMCL) prepared in Preparation Example 1.1 above through in-situ FTIR real-time tracking. 10 DA) and different proportions of the rheology modifier PEG obtained from Preparation Example 2.1 22 Curing kinetics and monomer reaction kinetics of SH-based mercapto-acrylate polymer inks under 365 nm UV irradiation.
[0188] 1) Curing kinetics test:
[0189] A small amount of the different ratio of thiol-acrylate polymer ink prepared in Example 3 was added between two NaCl crystals, and then placed vertically in the sample chamber for photopolymerization, which was initiated by a 365 nm UV light source, and OMNIC software was used to collect data, a DTGS KBr detector was used to measure signal intensity, and scanning was recorded at a scan rate of 1 per second, wherein the light intensity was 50 mW / cm 2 .
[0190] Figure 10 The in-situ infrared three-dimensional continuous spectrum of the photopolymerization process of the ink with different ratios.
[0191] As can be seen from Figure 10 , the additive main body liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) prepared by Preparation Example 1.1 shows changes in the peak area of the C=C absorption peak at 1619 cm -1 and 1636 cm -1 in the in-situ infrared three-dimensional continuous spectrum, which indicates that the conversion rate of the liquid acrylate poly-4-methyl-ε-caprolactone (PMCL 10 DA) has changed.
[0192] Figure 11 The conversion rate curve of the double bond monomer in the photopolymerization process of the ink with different ratios.
[0193] As can be seen from Figure 11 , after the UV light source is turned on, the double bonds in the four different ratios of ink SH25, SH50, SH75 and SH100 are immediately converted, and there is basically no induction period, and the double bonds in the four inks are basically completely converted within 7 seconds, which provides a basis for the rapid solidification and molding of materials in the printing process, thereby ensuring the stability and accuracy of the printed components.
[0194] 2) Monomer reaction kinetics test:
[0195] This test is to obtain the curing kinetics of different formulations of thiol-acrylate polymer inks under 365 nm UV irradiation by real-time tracking of in-situ photorheology, and the specific operation is as follows:
[0196] A small amount of the different formulations of thiol-acrylate polymer ink prepared in Effect Example 3.3 was placed in a parallel plate, and an LED UV-vis accessory was used as a UV light source, and in shear oscillation mode, the test time was set to 240 seconds, the UV exposure time was 210 seconds, the light intensity was 50 mW / cm 2 , and the UV light was turned on at 30 seconds of the test.
[0197] Figure 12 In-situ optical rheology test figure of different formula ink light curing.
[0198] As can be seen from Figure 12 , in the absence of light, the loss modulus G" of the ink is greater than the storage modulus G', showing viscous characteristics; when the 365 nm ultraviolet light is turned on, the storage modulus G' of the ink rapidly increases within 10 seconds and exceeds the loss modulus G", the network gradually forms and shows solid characteristics, indicating that the different ratio series of mercapto-acrylate polymer inks prepared from effect example 3.3 can ensure to provide support for the subsequent structure during printing. Example 4
[0199] The embodiment provides a method for printing 3D biodegradable elastic members by using the series of mercapto-acrylate polymer inks DIW prepared from effect example 3.3.
[0200] The method provided by the embodiment comprises the following steps:
[0201] The ink is loaded into the nozzle material bucket of the DIW-3D printer, the printing parameters including layer height, nozzle travel speed, extrusion speed and nozzle temperature are set, and then printing is carried out under ultraviolet light irradiation, so that the required 3D biodegradable elastic member can be obtained.
[0202] To further help understand the technical solutions provided by the embodiment and the specific operation process of the embodiment and the technical effects that can be obtained, the following will further illustrate the method for printing 3D biodegradable elastic members by DIW and the effects provided by the embodiment through specific printing examples.
[0203] Of course, those skilled in the art should understand that the specific printing examples described below are only illustrative and not limiting, and should not limit the scope of protection required by the present application. Printing example
[0204] The series of inks of different ratios of mercapto-acrylate polymers prepared from effect example 3.3 are respectively loaded into the nozzle material bucket of the DIW-3D printer as shown in Figure 13 The nozzle material bucket of the DIW-3D printer as shown in the schematic diagram of the device and process for DIW printing of mercapto-acrylate polymer inks, and a 3D model of the pre-printed member is established through Biomaker software, and DIW printing is carried out under real-time ultraviolet light irradiation using a 25G nozzle with an inner diameter of 0.25 mm, wherein the printing parameters such as nozzle temperature, printing speed, extrusion speed, and layer height are set according to Table 3 and are adapted to the characteristics of different formula inks, the light source uses 365 nm ultraviolet light, the light intensity uses 50 mW / cm 2 .
[0205] Table 3
[0206]
[0207] Figure 14 Figures 1 to 8 show a photo gallery of different components printed using the thiol-acrylate polymer ink SH75 prepared in Example 3.3, with the "suitable" printing parameters provided in Table 3, wherein, Figure 14-1 a is 1 # a 3D model of the component, Figure 14-1 b is 1 # a photo of the component, Figure 14-2 a is 2 # a 3D model of the component, Figure 14-2 b is 2 # a photo of the component, Figure 14-3 a is 3 # a 3D model of the component, Figure 14-3 b is 3 # a photo of the component, Figure 14-4 a is 4 # a 3D model of the component, Figure 14-4 b is 4 # a photo of the component.
[0208] From Table 3 and Figure 13 , Figure 14 it can be seen that:
[0209] at a printing speed of 4 mm / s, suitable nozzle temperature, extrusion speed and layer height, the thiol-acrylate polymer ink SH75 prepared in Example 3.3 can be used to print components with complete structure and high precision (such as the 10 x 10 x 5 mm grid components 1 Figure 14 shown in Figures 1 to 4 # # # # ;
[0210] and experiments have shown that the thiol-acrylate polymer inks SH25 and SH50 prepared in Example 3.3 can also be used to print components with the same characteristics as Figure 14 the components shown in Figures 1 to 4
[0211] However, the ink SH100 has a larger viscosity, the nozzle is prone to blockage, and the structure of the printed components is less precise than the printed results of the other three inks, but all the components can be cured and formed under real-time irradiation of ultraviolet light.
[0212] To further help understand the printing scheme provided by the present embodiment and the technical effects that can be achieved by the present embodiment, the following further describes the characteristic effects of the 3D biodegradable elastic member printed by the ink provided by the present embodiment through a specific effect example.
[0213] Of course, those skilled in the art should understand that the effect examples specifically described below are only illustrative and not limiting, and should not limit the scope of protection claimed by the present application.
[0214] Before implementing the following effect example, 10 x 10 x 5 mm 3D grid members SH25-7, SH50-3 and SH75-4 were printed by the thiol-acrylate polymer inks SH25, SH50 and SH75 prepared by effect example 3.3 using the "suitable" printing parameters in table 3 as test samples. Effect Example 4.1
[0215] This effect example detects the cyclic compression performance of the above-mentioned 3D grid members SH25-7, SH50-3 and SH75-4 by a universal testing machine.
[0216] Detection method:
[0217] The above-mentioned test samples SH25-7, SH50-3 and SH75-4 were tested (n = 3) by a universal testing machine, wherein the test rate was 10 mm / min, the compression cycle number was 10 times, and the compression deformation amount was 50 %.
[0218] Figure 15 The cyclic compression performance test chart of the 3D grid members SH25-7, SH50-3 and SH75-4.
[0219] From Figure 15 it can be seen that the 10 x 10 x 5 mm thiol-acrylate 3D grid members printed by the thiol-acrylate polymer inks SH25, SH50 and SH75 prepared by effect example 3.3 using the DIW according to the above-mentioned test method, each only showed a slight hysteresis phenomenon within 10 compression cycles;
[0220] In addition, the peak value of stress in each cycle remained basically unchanged, indicating that the members printed by the thiol-acrylate polymer inks SH25, SH50 and SH75 prepared by effect example 3.3 using the DIW had excellent elasticity and fatigue resistance at room temperature, which could ensure that the stent recovered well after deformation. Effect Example 4.2
[0221] This example provides the contact angle test results for the above-mentioned 3D mesh components SH25-7, SH50-3, and SH75-4.
[0222] Test method:
[0223] The above-mentioned 3D mesh components SH25-7, SH50-3 and SH75-4 were placed in a contact angle measuring instrument for hydrophilicity and hydrophobicity testing (n=3).
[0224] Figure 16 The contact angle test diagrams are for the above-mentioned 3D mesh components SH25-7, SH50-3 and SH75-4.
[0225] from Figure 16 It can be seen from this:
[0226] In Example 3.3, the 3D mesh components printed with the thiol-acrylate polymer ink prepared by SH25-7 showed the largest contact angle (93.2°), SH50-3 had a moderate contact angle (65.5°), while SH75-4 had the smallest contact angle (48.0°). This indicates that the hydrophilic rheology modifier PEG... 22 When SH is added to the ink, it simultaneously increases the hydrophilicity of the component, and the hydrophilicity increases with the amount of PEG in the ink formulation. 22 The number of SH items increases as the number of SH items increases. Example of effect 4.3
[0227] This example provides the in vitro degradation results of the above-mentioned 3D mesh components SH25-7, SH50-3 and SH75-4.
[0228] Test method:
[0229] The above-mentioned 3D mesh components SH25-7, SH50-3 and SH75-4 were placed in PBS buffer solution with pH=7.4 and containing 250 U / mL lipase to form test samples;
[0230] The PCL / poly-ε-caprolactone membrane with an Mn of 80000 obtained by hot pressing was placed in PBS buffer solution with pH=7.4 and containing 250 U / mL lipase to form a test control.
[0231] Then, the test samples and test controls were placed together in a constant temperature shaking incubator at 37°C for the degradation experiment. The shaking speed of the constant temperature shaking incubator was set to 150 r / min, and the enzyme solution was changed every two days. The test samples and test controls (n=3) were collected at preset time points, washed with deionized water, and then freeze-dried to obtain the degraded 3D mesh components and PCL / poly-ε-caprolactone membrane.
[0232] Figure 17In vitro degradation curve of the 3D meshwork member SH25-7, SH50-3, SH75-4 and PCL / poly-ε-caprolactone film.
[0233] It can be seen from Figure 17 that:
[0234] The thiol-acrylate 3D meshwork member printed by the thiol-acrylate polymer ink SH25, SH50 and SH75 prepared in Example 3.3 using DIW has a complete degradation within 20 days, while the PCL / poly-ε-caprolactone film with Mn of 80000 has a complete degradation within 25 days, which shows that the addition of the rheological modifier PEG 22 increases the hydrophilicity of the meshwork member printed by the thiol-acrylate polymer ink prepared in Example 3.3, so that water and enzymes can more easily penetrate the member, thereby accelerating the degradation of the member. Example 4.4
[0235] This example evaluates the influence of the above-mentioned 3D meshwork member SH25-7, SH50-3, SH75-4 on the proliferation of L929 cells (commercial product) by CCK-8 cell viability detection method.
[0236] Test method:
[0237] The above-mentioned 3D meshwork member SH25-7, SH50-3, SH75-4 is respectively placed in a 24-well plate, 250 μL of cell suspension is added to each well, and the cell density in each well is 1.5 x 10 4 The sample in the experimental group is composed; under the same experimental conditions as the composition of the experimental group, a 3D scaffold printed by PCL (M n = 80000) is used as a sample in the control group instead of the above-mentioned 3D meshwork member;
[0238] The sample in the experimental group and the sample in the control group are respectively placed in an incubator for co-culture, and after the 1st, 3rd and 7th days of co-culture, the original culture medium is removed, and the sample is washed with PBS solution for 3 times, then CCK-8 is prepared into CCK-8 culture solution according to the ratio of reagent: culture medium = 1:9, 200 μL of which is added to the sample in the experimental group and the sample in the control group respectively, and then the sample is placed in a 37℃ incubator for incubation in the dark for 1 hour, then 100 μL of liquid is taken from each well and added to a new 24-well plate, and the absorbance at 450 nm is measured by an enzyme marker (n = 3).
[0239] Figure 18 In vitro cell proliferation column chart of the 3D meshwork member SH25-7, SH50-3, SH75-4 and PCL / poly-ε-caprolactone film.
[0240] From Figure 18 It can be seen that:
[0241] The cell growth trend of the 10 x 10 x 5 mm thiol-acrylate 3D grid members and the 3D scaffolds prepared from PCL printed by using the thiol-acrylate polymer inks SH25, SH50 and SH75 prepared in Preparation Example 3.3 with DIW is good, and the OD value increases with time, indicating that the 3D grid members and the 3D scaffolds prepared from PCL have no effect on the proliferation of L929 cells;
[0242] In addition, the cell viability of the 3D grid member SH75-4 is higher than that of the 3D scaffolds prepared from PCL and the 3D grid members SH50-3 and SH25-4, and since the PEG content in the 3D grid member SH75-4 is the highest, the hydrophilicity of the member is increased, and the cell adhesion is easier, indicating that the members obtained by 3D printing of the thiol-acrylate polymer inks SH25, SH50 and SH75 prepared in this use effect example 3.3 have good cell compatibility.
[0243] It should be particularly noted that:
[0244] In addition, although the above examples, preparation examples and effect examples are based on the preferred technical solutions disclosed in the present application, experiments have proved that for all other technical solutions disclosed in the present application, including all feeding ratios and all process control parameters (ranges), or various other materials disclosed in the present application, such as liquid ultraviolet light initiator Irgacure 184, DMPA, etc., the products obtained therefrom can also obtain the same or basically the same technical effects as described above. The present specification is only for the sake of brevity and does not repeat and pile up the related test data and drawings, and is only a representative description based on the above examples, preparation examples and effect examples. Therefore, it can be understood that the above description cannot be regarded as a limitation on the protection scope of the present application.
[0245] In the description of the above specification:
[0246] The terms "the present embodiment", "the present embodiment of the application", "the present case", "the present comparative example", "as shown", "further" and the like mean that the specific features, structures, materials or characteristics described in the embodiment or case, comparative example are contained in at least one embodiment or case and comparative example of the present application;
[0247] In the present specification, the illustrative description of the above-mentioned terms is not necessarily directed to the same embodiment or case, comparative example, and the specific features, structures, materials or characteristics described can be combined or combined in any one or more embodiments or cases, comparative examples in a suitable manner; in addition, the ordinary skilled in the art can also combine or combine the different embodiments or cases, comparative examples and the features in different embodiments or cases, comparative examples described in the present specification without generating contradictions.
[0248] Finally, it should be noted that:
[0249] The above examples and comparative examples are only used to illustrate the technical solutions and technical effects of the present application, and are not limited thereto; although the present application has been described in detail with reference to the foregoing examples and cases, comparative examples, those skilled in the art should understand that it can still modify or supplement the technical solutions or technical effects described in the foregoing examples and cases, comparative examples, or make equivalent replacement for part or all of the technical features, and these modifications or replacements cannot make the essence of the corresponding technical solution deviate from the scope of the technical solution set forth by the embodiments of the present application, and the non-essential improvements and adjustments or replacements made by the skilled in the art according to the content of the present specification are all within the scope of the present application.
Claims
1. A mercapto-acrylate polymer system ink, comprising the following components: liquid acrylate poly 4-methyl-ε-caprolactone, thiol-functionalized polyethylene glycol and ultraviolet light initiator; wherein the molar ratio of liquid acrylate poly 4-methyl-ε-caprolactone to thiol-functionalized polyethylene glycol is 1: (0.25-1.0); the liquid acrylate poly 4-methyl-ε-caprolactone has the following structure: and m + n is 10 to 50; the thiol-functionalized polyethylene glycol has the following structure: and x = 22.
2. The mercapto-acrylate polymer system ink according to claim 1, characterized in that, wherein the molar ratio of liquid acrylate poly 4-methyl-ε-caprolactone to thiol-functionalized polyethylene glycol is 1: (0.25-0.75).
3. The mercapto-acrylate polymer system ink according to claim 2, characterized in that: wherein the ultraviolet light initiator used is selected from one or more of Irgacure 184, TPO-L and DMPA.
4. A preparation method of the mercapto-acrylate polymer system ink according to any one of claims 1-3, mainly comprising the following step: mixing the liquid acrylate poly 4-methyl-ε-caprolactone, the thiol-functionalized polyethylene glycol and the ultraviolet light initiator to obtain the product. wherein: the mass of the ultraviolet light initiator accounts for (0.95-1.05)% of the mass of the liquid acrylate poly 4-methyl-ε-caprolactone used.
5. The method of claim 4, wherein: wherein the liquid acrylate poly 4-methyl-ε-caprolactone is prepared by a preparation method comprising the following steps: under the condition of ice water bath, a dichloromethane solution of 4-methylcyclohexanone is dropped into a dichloromethane solution of meta-chloroperoxybenzoic acid at a constant speed, wherein the mass ratio of 4-methylcyclohexanone to meta-chloroperoxybenzoic acid is 1: (1.5-3), after the dropping is completed, the reaction is carried out at room temperature for 24 hours to obtain 4-methyl-ε-caprolactone; under the protection of argon, 1,4-benzenedimethanol is mixed with 4-methyl-ε-caprolactone at a molar ratio of 1: (10-50), and 0.1% of isooctoate stannous by the mass of 4-methyl-ε-caprolactone is added, and the polymerization reaction is carried out at a temperature of 120-140℃ for 6-24 hours to obtain poly 4-methyl-ε-caprolactone; under the condition of ice water bath, a dichloromethane solution of acryloyl chloride is dropped into a dichloromethane solution of the poly 4-methyl-ε-caprolactone and triethylamine at a constant speed, wherein the molar ratio of the poly 4-methyl-ε-caprolactone to the acryloyl chloride and the triethylamine is 1: (2.2-3): (2.0-3.0), after the dropping is completed, the reaction is carried out at room temperature for 24 hours to obtain the target product.
6. The method of claim 4, wherein: wherein the thiol-functionalized polyethylene glycol is prepared by a preparation method mainly comprising the following steps: polyethylene glycol and mercaptopropionic acid are dissolved in toluene, a catalytic amount of concentrated sulfuric acid is added, and the reaction is carried out at 90-130℃ under reflux for 12-24 hours to obtain the target product; wherein the polyethylene glycol has a number average molecular weight of 1000, and the molar ratio of the polyethylene glycol to the mercaptopropionic acid is 1: (4-6).
7. Use of the mercapto-acrylate polymer system ink according to any one of claims 1-3 as a direct ink writing (DIW) printing ink.
8. A method for preparing a 3D biodegradable elastic member by using the thiol-acrylate polymer system ink according to any one of claims 1 to 3 for DIW printing, comprising the following steps: loading the ink into a nozzle cartridge of a DIW-3D printer, setting parameters including printing layer height, nozzle travel speed, extrusion speed and nozzle temperature, and then printing under ultraviolet light irradiation to obtain the 3D biodegradable elastic member.
9. A 3D biodegradable elastomeric member, characterized by, prepared by the method of claim 8.